2002
DOI: 10.1039/b111192m
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentations and reactions of three isotopically labelled dimethyl methylphosphonate ions produced by electrospray ionisation in an ion trap mass spectrometer

Abstract: In an initial investigation into the electrospray ionisation ion trap mass spectrometry (ESI/ITMS) of simple organophosphate esters we reported that in one of the collision induced fragmentation steps of protonated dimethyl methylphosphonate (DMMP), formaldehyde was eliminated with a concomitant partial scrambling of the methyl group attached to the phosphorus and a methoxy group. The present paper describes a further investigation of this reaction. Three novel isotopomers of DMMP were used for this study and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…The mass spectrometric techniques and experimental conditions used in the present work have been describedóinódetailóelsewhereó [2]óbutóinóthisóworkóonlyóthe EsquirẽLC, Bruker Daltonics, GmbH (Bremen, Germany) was used. All ions were isolated before fragmentation, thus removing ambiguity in the precursor-fragment ion relationships.…”
Section: Mass Spectrometrymentioning
confidence: 99%
See 1 more Smart Citation
“…The mass spectrometric techniques and experimental conditions used in the present work have been describedóinódetailóelsewhereó [2]óbutóinóthisóworkóonlyóthe EsquirẽLC, Bruker Daltonics, GmbH (Bremen, Germany) was used. All ions were isolated before fragmentation, thus removing ambiguity in the precursor-fragment ion relationships.…”
Section: Mass Spectrometrymentioning
confidence: 99%
“…nvestigations of the fragmentations and reactions of the ions of simple organophosphate esters produced by electrospray ionization (ESI) in an ion trap (IT) mass spectrometer demonstrated that detailed structural information could be obtained by sequential Collision Induced Dissociation (CID) [1][2][3]. These studies have been extended to more complex organophosphates such as the chemical warfare [4], and organophosphate insecticides, one of which Diazinon I, together with its oxygen analog Diazoxon II, and pyrimidinol side-chain III, are the subject of the present paper (see Figure 1 for structures).…”
mentioning
confidence: 99%
“…To gain an understanding of the gas‐phase fragmentation mechanisms, the analytes need to contain a label that can be followed through the various MS transitions. One method that has been useful in elucidating fragmentation mechanisms is the exchange of acidic hydrogen atoms for deuterium atoms in solution,3–5 isotopically labelling the analytes in specific, known positions. GLYP and AMPA are particularly amenable to this type of analysis due to their ionisable groups and aqueous solubility.…”
mentioning
confidence: 99%
“…Therefore, we propose a substitution of the S‐atom by water during the mass spectrometric fragmentation process in the ion trap mass analyzer. Such a phenomenon has been described before by Bell et al for the organophosphorus nerve agent VX and pyrophosphonate and for trimethyl phosphate and diisopropyl methylphosphonate, as well as by Barr et al for dimethyl methylphosphonates . We would like to propose the mechanism presented in Figure explaining the production of the ion at m/z 143.1 by fragmentation of the protonated pesticide.…”
Section: Resultsmentioning
confidence: 99%
“…Such a phenomenon has been described before by Bell et al for the organophosphorus nerve agent VX and pyrophosphonate 24 and for trimethyl phosphate and diisopropyl methylphosphonate, 25 as well as by Barr et al for dimethyl methylphosphonates. 26 We would like to propose the mechanism presented in Figure 3 explaining the production of the ion at We also tested whether the presence of the ion at m/z 144.2 could be due to the presence of a 13 C-isotope in DIM ( Figure 4B).…”
Section: Product Ion At M/z 1432mentioning
confidence: 99%